Sea-ice distribution and ocean temperature variation in the Powell Basin and Scotia Sea, inferred from marine sediment cores PS118_63-1 and PS67/219-1 - Wee Wei Khoo; Oliver Esper; Wenshen Xiao; Jens Hefter; Juliane Müller (PANGAEA, 2025)
Presently, there is a scarcity of coastal (paleo) sea-ice reconstructions for periods prior to the Last Glacial Maximum. In this study, we investigated sea ice and ocean temperature proxies from marine sediment core PS118_63-1 from the Powell Basin, NW Weddell Sea. Past sea-ice characteristics inferred from the sea-ice biomarker IPSO25, alongside phytoplankton biomarkers, TOC, biogenic opal estimates and diatom assemblages provide a continuous record of past sea-ice conditions and ocean temperature variability, back to the Penultimate Glacial (ca. 145 ka BP). Our results reveal a highly dynamic sea-ice environment, characterized by significant shifts from perennial (sea) ice cover to more seasonal sea-ice cover to open ocean conditions, with no significant glacial-interglacial ocean temperature variability in the Powell Basin. Furthermore, latitudinal tracking of sea-ice distribution and sea surface temperature differences is enabled when comparing diatom-inferred data from the marine sediment core PS67/219-1.